Effect of some sodium salts coatings on the high-temperature oxidation of Nimonic-80A alloy at 1173 K - Mohammed Misbahul, Amin (Elsevier Science B.V., 2009)
Link to publisher's homepage at http://www.elsevier.com/wps/find/homepage.cws_home